2015
DOI: 10.1124/dmd.114.062901
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution of Etanercept to Tissues and Sites of Inflammation in Arthritic Rats

Abstract: Many monoclonal antibodies (mAbs) and other protein drugs have targets usually residing within tissues, making tissue concentrations of mAbs relevant to their pharmacologic effects. Therefore, knowledge of tissue distribution kinetics is important to better understand their pharmacokinetics and pharmacodynamics. The tissue distribution of mAbs is affected by many physiologic factors that may be altered in disease status. In the present work, we studied the tissue distribution kinetics of the fusion protein eta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
(40 reference statements)
5
6
1
Order By: Relevance
“…The estimated vascular reflection coefficients ( σ j_ctrl and σ j_CIA ) suggest twofold increase of vascular permeability in CIA mice. This corresponds well with our previous study showing that inflammation causes increased vascular permeability and enhanced tissue distribution of etanercept in arthritic paws in CIA rats [19]. …”
Section: Discussionsupporting
confidence: 93%
“…The estimated vascular reflection coefficients ( σ j_ctrl and σ j_CIA ) suggest twofold increase of vascular permeability in CIA mice. This corresponds well with our previous study showing that inflammation causes increased vascular permeability and enhanced tissue distribution of etanercept in arthritic paws in CIA rats [19]. …”
Section: Discussionsupporting
confidence: 93%
“…Large molecule drugs abide by permeability‐rate‐limited distribution and are subject to vascular hyperpermeability in inflamed organs. To represent this effect, the pore sizes in inflamed organs were increased proportional to an inflammation factor in agreement with previous minimal PBPK models of inflammatory conditions by other studies that observed the requirement for lower vascular reflection coefficients in inflamed organs. The large intestine was inflamed in patients with inflammatory bowel disease, the bone was inflamed in patients with rheumatoid arthritis and ankylosing spondylitis, the skin was inflamed in patients with psoriasis, and the lungs were inflamed in patients with non‐small cell lung cancer.…”
Section: Methodssupporting
confidence: 82%
“…For etanercept, we were able to detect a placental concentration in one patient only, who received etanercept shortly (4 days) before delivery. Tissue distribution of etanercept in rats was found to be 7–15% of plasma levels, depending on the type of tissue 23 . No placental tissue was studied, but the order of magnitude of tissue exposure appears in line with the placental distribution of approximately 3% of the plasma concentration that we report here.…”
Section: Discussionsupporting
confidence: 70%